TRANMISI KEILMUAN PENDIDIKAN DI INDONESIA Perspektif Kurikulum Kompetensi Berbasis Karakter - kulsum, Ummu (Universitas Islam Madura, 2016)
Education is a human need in life, with education could see the horizon of life. Education has many models adopted by mankind in this hemisphere, depending on the ultimate goal of education. In Indonesia adheres to education set by the Act and the government's resolve either of national or local regulations. The policies introduced by the government should make the concept of the curriculum as a substance, as a system, and as a field of study. MONE Strategic Plan 2010-2014 had a vision in 2025 to produce and competitively Smart Insan Indonesia (Insan Kamil / Insan Plenary). Insan Indonesia Smart is a comprehensive intelligent human being, namely the spiritual intelligent, emotionally intelligent, socially intelligent, intellectually smart, and intelligent kinesthetic. Competency-based curriculum characters, previously existing CBC, but only based on competency, so then felt nothing less than the curriculum. So the character is the answer. Characters like foundations and competence is building that stands on these competencies. They all die to whether there is a willingness to change (willingness to change) from key stakeholders such education, especially teachers.